Reproductive health knowledge and self-efficacy of female young adults in selected coastal communities - Detoyato, Charlemagne O.; Villanueva, Karla L. (2004.)
This study aimed to find out ig there is a relationship between reproductive health knowledge and self-efficacy of female young adults. Specifically this was designed to: 1)know the level of reproductive health knowledge of female young adults; 2)determine their level of self-efficacy; and 3)find out if there is an existing relationship between, reproductive health knowledge and self-efficacy of young adults. One hundred three (103) young adults from selected barangays of Dumangas was randomly chosen to serve as respondents of the study. The Reproductive Health Knowledge Questionnaire and the Self-efficacy Scale provided by the Youth Survey Bank was utilized in data gathering., Results revealed that female young adults have low reproductive health knowledge with a mean score of 53.835 as obtained in their Reproductive Health Knowledge Questionnaire scores. On the other hand, all of the respondents exhibited a high level of self-efficacy, as reflected by the mean score of 82.136 based on their answers in the Self-Efficacy Scale. Furthermore, it wa showed by the Pearson-Product Momemt Correlation that reproductive health knowledge and self-efficacy of the female young adults respondents has an existing relationship. with one hundred one (101) degrees of freedom (df=103-2) and the correlation coefficient value of 0.049 at reliability level of 0.05, the statistical analysis showed that the value (0.049>P.196) is below the tabled value of 0.05; Thus correlation is not significant. The researchers suggest that proper information dissemination on reproductive health issues will be facilitated. further research about the topic is also recommended.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Young adluts -- Female -- Reproductive Health Knowledge